Multifunctional applications of biochar beyond carbon storage. (17th February 2022) - Bolan, Nanthi; Hoang, Son A.; Beiyuan, Jingzi; Gupta, Souradeep; Hou, Deyi; Karakoti, Ajay; Joseph, Stephen; Jung, Sungyup; Kim, Ki-Hyun; Kirkham, M.B.; Kua, Harn Wei; Kumar, Manish; et al.
ABSTRACT: Biochar is produced as a charred material with high surface area and abundant functional groups by pyrolysis, which refers to the process of thermochemical decomposition of organic material at elevated temperatures in the absence of oxygen. The carbon component in biochar is relatively stable, and, hence, biochar was originally proposed as a soil amendment to store carbon in the soil. Biochar has multifunctional values that include the use of it for the following purposes: soil amendment to improve soil health, nutrient and microbial carrier, immobilising agent for remediation of toxic metals and organic contaminants in soil and water, catalyst for industrial applications, porous material for mitigating greenhouse gas emissions and odorous compounds, and feed supplement to improve animal health and nutrient intake efficiency and, thus, productivity. This article provides for the first time an overview of the multifunctional values and unintended consequences of biochar applications.